ACL Function in Bicruciate-Retaining Total Knee Arthroplasty. (5th September 2018) - Okada, Yohei; Teramoto, Atsushi; Takagi, Tetsuya; Yamakawa, Satoshi; Sakakibara, Yuzuru; Shoji, Hiroaki; Watanabe, Kota; Fujimiya, Mineko; Fujie, Hiromichi; Yamashita, Toshihiko
Abstract : Background: Bicruciate-retaining total knee arthroplasty (BCR-TKA) is attracting attention because of the functional and satisfaction outcomes associated with keeping the anterior cruciate ligament (ACL) intact. However, knowledge of the functional importance of the ACL after BCR-TKA is limited. We performed a biomechanical investigation of ACL function following BCR-TKA compared with that in the intact knee. Methods: We investigated 8 fresh-frozen human cadaveric knees using a 6-degrees-of-freedom robotic system that allowed natural joint motion. Three knee states—intact knee, BCR-TKA, and BCR-TKA with ACL transection (BCR-TKA + ACLT)—were evaluated. For each knee state, the kinematics during passive flexion-extension motion (from 0° to 120°) and anteroposterior laxity at 0°, 15°, 30°, 60°, and 90° of flexion in response to a 100-N load were investigated. The recorded knee motions of the intact and BCR-TKA knees during each test were repeated after ACLT to calculate the ACL in situ force. Results: The femur in the BCR-TKA group translated posteriorly and rotated externally during passive knee flexion and was in an anterior position compared with the femur in the intact-knee state. After ACLT, the femur translated posteriorly, compared with the BCR-TKA group, at 0° and 10° (p < 0.05). The anteroposterior laxities of the BCR-TKA and intact knees were comparable at all flexion angles and increased 2-fold or more after ACLT (p < 0.01). The ACL in situ force in the BCR-TKA knees was 2-fold to 6-fold higher than that in the intact knees at 0°, 15°, 90°, and 120° during a passive path (p < 0.05) and equivalent to that in the intact knees under anterior loading. Conclusions: The preserved ACL in the BCR-TKA knees was functional, like the ACL in the intact knees, under anterior tibial loading and contributed to good anteroposterior stability. However, the kinematics and ACL in situ force differed between the intact and BCR-TKA knees during passive flexion-extension movements. Clinical Relevance: Surgeons may not be able to prevent overtensioning of the ACL during a standardized BCR-TKA procedure, which could potentially limit range of motion.